1992
DOI: 10.1007/bf02698504
|View full text |Cite
|
Sign up to set email alerts
|

A cry unheard: Sudden reductions in blood pressure while talking about feelings of hopelessness and helplessness

Abstract: This paper describes sudden extreme drops in blood pressure in both experimental and clinical situations when a person is talking about or describing situations of hopelessness and helplessness. These changes are discussed in the context of historical perspectives about the cardiovascular system. A new perspective is introduced, one in which these blood pressure changes are seen as part of an unheard cry for understanding. It is hypothesized that such changes do not occur in response to a person's attempts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…According to Rowe (1986) a totally hopeless person does not need to use violence to die, supporting the idea that hope is present in suicidal ideation and supporting the idea that suicide is possible in despair (see also Engel 1968). Lynch et al. (1993) found sudden reductions in blood pressure while people were talking about hopelessness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Rowe (1986) a totally hopeless person does not need to use violence to die, supporting the idea that hope is present in suicidal ideation and supporting the idea that suicide is possible in despair (see also Engel 1968). Lynch et al. (1993) found sudden reductions in blood pressure while people were talking about hopelessness.…”
Section: Discussionmentioning
confidence: 99%
“…According to Rowe (1986) a totally hopeless person does not need to use violence to die, supporting the idea that hope is present in suicidal ideation and supporting the idea that suicide is possible in despair (see also Engel 1968). Lynch et al (1993) found sudden reductions in blood pressure while people were talking about hopelessness. They interpret the findings in the following way: the blood pressure reductions represent the biological foundations of hopelessness; reductions are not responses to the person's attempts to communicate their sense of hopelessness.…”
Section: Issues In Clinical Nursingmentioning
confidence: 99%
“…The simple act of communication (talking or sign language) is routinely accompanied by an increase in blood pressure within 30 s. In contrast, when patients allude to feelings of extreme hopelessness or helplessness, the BP can suddenly drop by as much as 50%. 28 In this patient, therapy was focused progressively on postural stress of standing, expression of anger in a modulated fashion, and other covert affective struggles. The patient subsequently reported that 'she slowly began to learn what her body felt like when her blood pressure was going down ... learned to recognize stress triggers that caused her pressure to fall ... learned methods of elevating pressure in the autonomic laboratory by doing simple mathematics, moving, talking, etc.'…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we put forward a theoretical framework in an attempt to broadly conceptualize many of the CVR findings (Lyons, Spicer, Tuffin, & Chamberlain, 2000). According to this account, the consistent elevations that are evident in cardiovascular functioning during talking (e.g., Lynch, Lynch, & Friedmann, 1992;Stein & Boucher, 1993) or any form of communication, including sign language (Malinow, Lynch, Foreman, Friedman, & Thomas, 1986) might be conceptualized as a correlate of self-construction processes. We suggested that talking engages the speaker in many ways and that this engagement might manifest itself in physiological processes, such as CVR.…”
mentioning
confidence: 99%